Bio-screening and quantification of methyl paraben in vinegar and coconut juice separated by HPTLC - Yisheng Chen; Xingjun Xi (Food Science and Human Wellness)
As a widely used food preservative, methyl paraben was experimentally evidenced with serious hormonelike adverse effects. Herein, a high performance thin-layer chromatography platformed bioluminescent bioautography and image analysis for the selective quantification and confirmation of methyl paraben was proposed and validated in vinegar and coconut juice. First, the detectability of the bioautography to the analyte on different layer materials was estimated, revealing that normal silica gel was the best choice. After that, the liquid of sample extract and working solution were separated to overcome the background noises due to co-extracted matrices. The separation result was then coupled to the optimized bioautography, enabling instant and straightforward screening of the targeted compound. For accurate quantification, bioluminescent inhibition pattern caused by the analyte was processed by image analysis, giving useful sensitivity (LOD > 16 mg/kg), precision (RSD < 10.1%) and accuracy (spike-recovery rate 76.9%–112.2%). Finally, the suspected result was confirmed by determining its MS fingerprint, further strengthening the reliability of screening.